Co-producing a shared understanding and definition of empowerment with people with dementia - Tracey McConnell (Research Involvement and Engagement, 2019)
Abstract Background Empowerment for people with dementia (PWD) is not well defined within the research literature and we feel that this is an important area for development. It is important to seek, consult, and co-produce such a definition with PWD who are more actively involved in their communities post diagnosis (e.g. no longer the ‘long goodbye’). This study seeks to combine academic literature review methods with participatory/co-production methods in order to address this gap. We feel this approach also adds to developing methodologies in the field of co-production and user involvement. Methods We use a unique approach toward a definition of empowerment for PWD. Phase 1 - A scoping review of medical/health, social care and social policy-based databases to identify any previous literature that may have defined empowerment exclusively for PWD. Based on this literature, we collected a list of terms relating to empowerment for PWD. Phase 2 – Using empowerment key terms set on cards formulated from Phase 1 across three co-production workshops, academic team members, and nine members of Dementia NI (an organisation founded and led by people with dementia) we reviewed the findings of this search and co-produced an agreed definition they felt best described empowerment for them. Results Phase 1 and 2 led to a definition of empowerment relevant to PWD. This shared understanding of empowerment was defined by PWD as ‘A confidence building process whereby PWD are respected, have a voice and are heard, are involved in making decisions about their lives and have the opportunity to create change through access to appropriate resources’. Conclusions The strength of this research lies in addressing the current confusion and arbitrariness of empowerment within the context of dementia. This coproduced work also provides evidence for not only the possibility, but also the added value of involving PWD in research in terms of unique insights afforded by their lived experiences.